Valuation of Plant & Equipment by the Industrial Development Corporation in South Africa (IDC) - Chadyiwa, Tinotonga (My University, 2012)
This research was primarily aimed at identifying and reviewing the use of depreciation factors when undertaking valuation of plant and machinery assets, particularly those under security. This will guide the changes that the Industrial Development Corporation (IDC) should implement in dealing with the uncertainties which arise when valuing plant and equipment and in improving security from current and prospective operational clients. The research will Identify possible losses from liquidation of current and prospective operational clients and propose suitable valuation procedure for equipment to be secured. The researcher conducted a case study survey from the IDC’s operational strategic business units (SBUs) employees. The data for the research was collected using a questionnaire in a structured survey format and examining current records on trends with regards to the propositions. For each of the SBUs, copies of well-structured questionnaires were given to an account manager. The study also sampled valuation reports prepared by valuers at IDC. The contents of valuation reports were examined and compared with data recovered by IDC after a client default. The researcher noted that recoveries from physical collateral generally lagged behind expected recoveries as reported in valuation reports. There were, however, mixed responses on the certainty and uncertainty of valuation figures reported. The key findings were that there was a need to re-look at the factors considered in the valuation practice. The recognition of appraisal depreciation considers the progressive decline in value as operational use and changes to the technical and economic environment diminish the worth of an asset. The expected asset retirement profile with its influence on life characteristics, in addition to the applied operation and maintenance policies, influences the rate of asset depreciation. These factors play a critical role in making sound estimates as far as valuation is concerned.
MBA thesis (WBS)
Keywords: Valuation of plant; Valuation of equipment; Industrial development corporation